The tadpole of Physalaemus henselii (Peters) (Anura: Leiuperidae) - Kolenc, Francisco; Borteiro, Claudio; Tedros, Marcelo; Núñez, Diego; Maneyro, Raúl (Zootaxa, 2006)
Although Physalaemus frogs are prominent members of Neotropical herpetofauna, larval stages are not known from more than half of the species in this genus. Herein, we describe the tadpole of Physalaemus henselii based on samples collected in Departamento de Rivera, northern Uruguay. General aspect and major external morphological features are similar to most of other known tadpoles of Physalaemus. Remarkable character states are a medial vent tube and the presence of dorsal and ventral gaps in the row of marginal oral papillae. Physalaemus henselii has been successively assigned to the P. cuvieri and to the P. henselii species groups, but no conclusions can be drawn in support of these associations from external larval morphology. Instead, we found that some character states may contribute to relate species, like the presence of a ventral gap in the marginal row of oral papillae which is shared by P. albonotatus, P. cuqui, P. cuvieri, P. fernandezae and P. henselii. This character state is unique among non-bufonid anurans, although it is also present in some species of the related genus Pseudopaludicola. In addition, P. albonotatus, P. cuqui and P. cuvieri tadpoles can be differentiated from P. fernandezae and P. henselii by the presence of two small ventrolateral gaps, which are absent in the latter.